A disaster resilient built environment in urban cities. Issue 1 (9th February 2015) - Jerry Velasquez, Dr; Malalgoda, Chamindi; Amaratunga, Dilanthi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This research aims at making recommendations to empower the Sri Lankan local governments in creating a disaster resilient built environment. Disasters make a huge impact on the built environment. In turn, failure of the built environment can create significant impacts on social and economic activities. Thus, when moving towards safer cities, it is important to develop the built environment in such a way that it can withstand threats posed by natural disasters. Various stakeholders need to get involved in the process of making a disaster resilient built environment, of which the local governments need to play a critical role, as they are the closest government body to the local community. However, local governments are facing a number of challenges in responding to city resilience activities. Design/methodology/approach – The research adopts case studies as its research strategy and investigates three cities in Sri Lanka which are potentially vulnerable to disasters. A number of expert interviews have also been conducted to supplement the case study findings. Findings – The paper presents the challenges faced by the Sri Lankan municipalities in creating a disaster resilient built environment and provides recommendations to empower municipalities to effectively contribute to city resilience. The paper suggests amending policies related to establishment of municipal councils and disaster management to provide more authoritative powers for municipalities to effectively engage in city resilience building. Findings also revealed the importance of addressing financial and human resource issues, which were the main drivers of hindrance. Furthermore, all relevant urban development plans, risk maps, disaster resilient planning, construction and operation guidelines and resilient land use practices need to be integrated into existing planning and building regulations, and proper monitoring and control mechanisms have to be established to ensure compliance with the regulations. In doing so, it is important to raise awareness of council officials of disaster risks and resilient practices by way of organising educational programmes such as seminars and workshops. It is also suggested that municipal officials should be involved in national-level decision-making with regard to their local areas and to establish proper communication channels to exchange decision and information related to city resilience. Research limitations/implications – The paper is based on case studies in three cities and a number of expert interviews, which are limited to the Sri Lankan context. Inputs from other cities from developed countries may further validate the recommendations. Originality/value – The paper highlights the challenges faced by the local governments in creating a disaster resilient built environment within Sri Lankan cities and provides recommendations as to how the local governments could be empowered in creating a disaster resilient built environment within cities.